Income Inequality in the 1990s: Comparing the United States, Great Britain and Germany - Richard V. Burkhauser; Ludmila Rovba (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Using data from the March Current Population Surveys in the United States, the Household Panel Survey in Great Britain and the Socio-Economic Panel in Germany we find gains from economic growth in the United States over their 1990s business cycle (1989-2000) were more equitably distributed than were the gains over their 1980s business cycle (1979-1989). Furthermore, they were more equitably distributed than were the gains in Germany over their 1990s business cycle (1991-2001). However, gains from economic growth in Great Britain over their 1990s business cycle (1990-2000) were the most equitably distributed. Our results hold using both summary measures of inequality as well as kernel density estimations. In the United States and Great Britain the entire income distribution moved upward in the 1990s. In Germany, as was the case in the United States over their 1980s business cycle, there was a drop in the middle of the income distribution and increases in both tails. In the United States, younger persons (aged 64 and younger) fared better than older persons (aged 65 and older) while the opposite was the case in Great Britain and Germany. Income inequality fell in all three countries among the older population. But it rose in Germany, remained about the same in the United States and fell in Great Britain among their younger populations.
Keywords: D3; 330; income inequality; kernel density estimations; economic well-being; cross-country comparisons